Lighting Modifiers Training In Food Photography For The MSME Fellow Pages Community: Pelatihan Penggunaan Lighting Modifier Untuk Fotografi Makanan Komunitas Fellow Pages - Tahalea, Silviana Tahalea; Jasjfi, Elda Franzia Jasjfi; Damarjati, FX. Damarjati (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
Since the COVID-19 pandemic, many small and medium enterprises (SMEs) in the homemade food and beverage sector have emerged as a means to sustain income. One of the main challenges they face is product marketing on social media, particularly in presenting appealing and appetizing food photos. In a previous community service program (PKM), UMKM Fellow Pages received photography training but continued to struggle with lighting and food styling techniques. Therefore, the author extended the training with a specific focus on food photography lighting, aiming to help SMEs produce more attractive and effective product photos for social media. Food has evolved into a form of visual art on social media, where appealing food photos can enhance desirability and appeal. Food photography has a long history, beginning with daguerreotype techniques in the 19th century and evolving into the use of food images in cookbooks and magazines in the 20th century. Today, food photography is a highly effective marketing tool in the digital age. Research indicates that visually appealing images can stimulate consumer desire to purchase. The UMKM Fellow Pages community aims to improve members' skills in lighting techniques through training on the use of lighting modifiers. With improved skills, SMEs can produce sharper, more accurate, and visually attractive product photos. This is expected to enhance product competitiveness in the digital marketplace, build brand identity, and ultimately increase sales and economic well-being.